Українське вишивання на Слобожанщині XIX-XX ст. - Сушко, В. (Народна творчість та етнографія, 2007)
This article is dedicated to traditions of embroidery art of Slobidska Ukraine throughout the period of the 19th and the 20th centuries. This art originates from the embroidery traditions of the regions the resettlers come from. By the beginning of the 19th century embroidery of Slobidska Ukraine had been already developed. Church and local fashion had influence on it. The author pays attention to the range, technique and ornaments of the embroidered garments of this period.